Associations between aspects of friendship networks and dietary behavior in youth: Findings from a systematized review. (August 2015) - Sawka, Keri Jo; McCormack, Gavin R.; Nettel-Aguirre, Alberto; Swanson, Kenda
Abstract: Objective: To gather and synthesize current evidence on the associations between aspects of friendship networks (e.g., friends' dietary behavior, popularity) and an individual's dietary behavior among children and adolescents. Methods: A systematic search of six scientific online databases was conducted in August 2013. Eligible studies included child or adolescent participants (aged 6 to 18 years), a measure of each participant's friendship network, and a measure of habitual dietary behavior for both the participant and the participant's nominated friend(s). Data on study design, participant characteristics, friendship networks, dietary behavior, and study outcomes were abstracted. Results: From a total of 9041 articles retrieved, seven studies were included in this review. Overall, friends' unhealthy food consumption was associated with an individual's unhealthy food consumption, and this association appeared to be stronger for boys compared with girls. More popular adolescents also tended to consume more unhealthy foods. Best friends' total energy intake was correlated with an individual's total energy intake. Similarities among friends' healthy food consumption, as well as daily breakfast consumption, were inconclusive. Longitudinal evidence showed that an individual's unhealthy food consumption tended to become similar to friends' unhealthy food consumption over time. Conclusions: Social network analysis in the adolescent dietary behavior literature is beginning to emerge. Results highlight friends' particular influence on unhealthy food consumption among adolescents. Focus on modeling healthy dietary behaviors among adolescent friendship group may help reduce unhealthy dietary behaviors and promote healthy weight status among youth. Highlights: Social network analysis in the adolescent diet literature is beginning to emerge. Friends' unhealthy diet behaviors are associated with individual's unhealthy diet behaviors. Longitudinal evidence showed similarities in unhealthy diet behaviors among friends over time. Similarities in friends' healthy diet behaviors were inconclusive.